Scabies in remote Aboriginal and Torres Strait Islander populations in Australia: A narrative review. - Prudence Gramp; Dallas Gramp (Public Library of Science (PLoS), 2021)
Scabies has recently gained international attention, with the World Health Organization (WHO) recognizing it as a neglected tropical disease. The International Alliance for the Control of Scabies recently formed as a partnership of more than 15 different countries, with an aim to lead a consistent and collaborative approach to preventing and controlling scabies globally. Scabies is most prevalent in low-resource and low socioeconomic areas that experience overcrowding and has a particularly high prevalence in children, with an estimated 5% to 10% in endemic countries. Scabies is widespread in remote Aboriginal and Torres Strait Islander communities in Australia with the prevalence of scabies in Aboriginal and Torres Strait Islander children in remote communities estimated to be as high as 33%, making it the region with the third highest prevalence in the world. This population group also have very high rates of secondary complications of scabies such as impetigo, poststreptococcal glomerulonephritis (PSGN), and rheumatic heart disease (RHD). This article is a narrative review of scabies in remote Aboriginal and Torres Strait Islander populations in Australia, including clinical manifestations of disease and current treatment options and guidelines. We discuss traditional approaches to prevention and control as well as suggestions for future interventions including revising Australian treatment guidelines to widen the use of oral ivermectin in high-risk groups or as a first-line treatment.